Plasma calprotectin level: usage in distinction of uncomplicated from complicated acute appendicitis. Issue 1 (December 2016) - Cikot, Murat; Peker, Kivanc; Bozkurt, Mehmet; Kocatas, Ali; Kones, Osman; Binboga, Sinan; Gedikbasi, Asuman; Alis, Halil
Abstract Background The aim of this study was to identify the diagnostic role of plasma calprotectin value for a distinction of presence acute appendicitis and the indifference of uncomplicated from complicated acute appendicitis. Methods Plasma calprotectin, white blood cell and C-reactive protein values of 89 patients, who have undergone laparoscopic appendectomy between January 2013 and May 2013 were evaluated. Results Calprotectin was 91 ng/mL (range 45–538) for acute appendicitis and 47 ng/ml (range 28–205) for the control group. There was a positive, statistically significant relation between calprotectin and C-reactive protein values (r  = 0. 292p  = 0. 001, respectively). There was no statistically significant difference was determined between calprotectin and white blood cell values (r  = 0. 142p  = 0. 187, respectively). CRP and Cal values were significantly higher in patients with a complicated AA group than in those with uncomplicated AA (p  = 0. 014, p  = 0. 0001, respectively) whereas white blood cell counts did not differ significantly between two groups (p  = 0. 164). Conclusion Plasma calprotectin levels were increased in patients with acute appendicitis and should use in a distinction of uncomplicated from complicated acute appendicitis patients.